Comparative study on bacterial cross-contamination between toothbrushes using pump-type and tube-type toothpaste dispenser - Pegenia, Joseph Glenn Z.
INTRODUCTION: Toothbrushes are expected to be manufactured free of microorganisms, but after a single use, varying from 30 seconds to 4 minutes, toothbrushes may become contaminated by a wide array of bacteria, viruses, yeast and fungi which are present in the oral cavity and in the environment. Studies show that microorganisms can remain viable on toothbrushes for long periods of time from 24 hours to 7 days depending on the organism that is present. In line with this, the use of contaminated toothbrush can be a way of transferring microorganisms intra-orally and from one person to another. A common practice among household today is the sharing of the same toothpaste dispenser among family members. Due to this, transmission of micro-organisms is possible because: 1) the regular use of toothbrushes will heavily contaminate them with microorganism; and 2) the orifice toothpaste dispensers is a source of cross-contamination especially when bristles come in contact with the orifice during toothpaste dispensing. Because of this, the researchers attempted to confirm if there is cross-contamination between toothbrushes using tube-type toothpaste dispenser and comparing it with another commercially available toothpaste dispenser which is the pump-type toothpaste dispenser.